Bolatkhan K., Akmuhanova N.R., Sadvakasova A.K., Bauenova M.O., Zayadan B.K. Toxins produced by cyanobacteria during ﬂowering water lake Bilikol: Toxins produced by cyanobacteria during flowering water lake Bilikol (Eurasian Journal of Ecology, 2018)
Study algocenoses of the lake Bilikol showed a preponderance of greenalgae on toxin and blue-green microalgae by frequency of occurrence. Species diversity of certain microalgae lake Bilikol belonged to the 4 divisions, 9classes, 9 orders, 17 families, 36 genera and 102 species. High species richness differed in the phytoplankton of the lake Bilikol green and blue-greenalgae, their number of species, varieties and forms is slightly more than halfof the taxonomic list (60% of the total). Cyanobacteria in the phytoplanktonof the lake Bilikol ranked second in species richness, and of the first. As aresult of the analysis of certain types of indicator-saprobity cyanobacterialake Bilikol we identified 12 species and varieties of indicator species of cyanobacteria. Modern combination chromatography and mass spectrometryare the most sensitive and selective methods of analysis of natural toxins,providing reliable identification. HPLC extracts of dried biomass of planktonic algae identified in lake Bilikol three structural variants hepatotoxic microcystins: Microcystin-RR, 7-Demethylmicrocystin RR and Microcystin-LR.Judging from the largest peak at chromatograms, in the study of biomass isdominated by Microcistina-LR. The presence of phytoplankton biomass microcystins in summer, obviously, connected with the active development ofcyanobacteria from birth by Microcystis, Anabaena, etc. It was determinedthat the «flowering» of the water of the lake Bilikol is not valid as recreationalreservoirs, because it threatens the health of people and animals.Key word: toxin, cyanobacteria, microalgae, algoflora, algocenos.